2017
DOI: 10.1016/j.ccell.2017.06.003
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor Evolution of Glioma-Intrinsic Gene Expression Subtypes Associates with Immunological Changes in the Microenvironment

Abstract: Summary We leveraged IDH wild-type glioblastomas, derivative neurospheres, and single cell gene expression profiles to define three tumor-intrinsic transcriptional subtypes designated as proneural, mesenchymal, and classical. Transcriptomic subtype multiplicity correlated with increased intratumoral heterogeneity and presence of tumor microenvironment. In silico cell sorting identified macrophages/microglia, CD4+ T lymphocytes, and neutrophils in the glioma microenvironment. NF1 deficiency resulted in increase… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

98
1,563
5
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,460 publications
(1,770 citation statements)
references
References 71 publications
98
1,563
5
6
Order By: Relevance
“…A total of 2,551 genes were differentially expressed, including genes involved in glial differentiation (Table S1), and Olig2 + tumors showed an enrichment of OPCs versus astrocytic genes (Figure 1B and Table S2) (Zhang et al, 2014). We compared gene expression in Olig2 + and Olig2 − mouse tumors with human OD and subtypes of GBM (Tirosh et al, 2016; Verhaak et al, 2010; Wang et al, 2017). As shown (Figures S1F, 1G, and Table S2), clustering analysis of differentially upregulated genes in Olig2 + (versus Olig2 − ) tumors indicated strongest association with human OD and proneural GBM gene profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 2,551 genes were differentially expressed, including genes involved in glial differentiation (Table S1), and Olig2 + tumors showed an enrichment of OPCs versus astrocytic genes (Figure 1B and Table S2) (Zhang et al, 2014). We compared gene expression in Olig2 + and Olig2 − mouse tumors with human OD and subtypes of GBM (Tirosh et al, 2016; Verhaak et al, 2010; Wang et al, 2017). As shown (Figures S1F, 1G, and Table S2), clustering analysis of differentially upregulated genes in Olig2 + (versus Olig2 − ) tumors indicated strongest association with human OD and proneural GBM gene profiles.…”
Section: Resultsmentioning
confidence: 99%
“…The p values were adjusted to account for multiple testing using the false discovery rate (FDR) approach, and probes with FDR p < 0.05 were considered to be differentially expressed. Genes up-regulated in Olig2 + tumors were compared to murine OPCs (versus astrocytic), human oligodendroglioma and GBM subtypes using published dataset (Tirosh et al, 2016; Verhaak et al, 2010; Wang et al, 2017; Zhang et al, 2014). Hierarchical clustering was performed using Gene Cluster 3.0 (de Hoon et al, 2004) and Treeview (Saldanha, 2004).…”
Section: Star⋆methodsmentioning
confidence: 99%
“…In our prior report, we found that GBM tumors of the mesenchymal subtype exhibited a statistically significant higher level of Fn14 expression when compared to the classical, neural, and proneural subtypes [4]. Of note, a recent report indicates that the neural subtype is not a tumor-intrinsic transcriptional subtype in IDH WT GBMs [44]. Here, we evaluated ~ 3× more tumor specimens and found that the Fn14 expression level was similar in the classical and mesenchymal subtypes although there was a trend toward higher expression in the mesenchymal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…26 The mutation status of gliomas is also associated with effects on the immune landscape of the tumor microenvironment, suggesting an impact on TAM protein expression in patient tumors. 27 A comparison of cores from IDH wild type and mutant tumors from our grade II-III TMA showed a slight increase in percentage of CD163 expressing cells in the IDH wild-type population (Figure 1E). Although it is tempting to speculate that CD163 infiltration may be associated with a poorer prognosis among these patients, the small sample size of wild type tumors (N = 3) precludes this conclusion and will be addressed in future studies evaluating a larger sample size.…”
Section: Resultsmentioning
confidence: 86%